Characterization of an Oncolytic Herpes Simplex Virus Drug Candidate. Issue 2 (31st October 2014) - Kumru, Ozan S.; Joshi, Sangeeta B.; Thapa, Prem; Pheasey, Nigel; Bullock, Paul S.; Bashiri, Houman; Siska, Christine S.; Kerwin, Bruce A.; He, Feng; Volkin, David B.; Middaugh, C. Russell
<x xml:space="preserve">Abstract</x> The structural integrity and conformational stability of a genetically modified live, oncolytic herpes simplex virus (o‐HSV) were investigated across a wide pH (5.5–8.0) and temperature (10°C–87.5°C) range. A combination of circular dichroism, intrinsic and extrinsic fluorescence, and static light scattering results was visualized using an empirical phase diagram approach to provide a global assessment of physical stability. Distinct phases were identified including the native state of the virus, an intermediate phase that could represent gradual swelling and/or shedding of the viral envelope, and a highly disrupted, aggregated phase. The nature of these altered forms of the virus was further evaluated by transmission electron microscopy and viral plaque assays. The effect of freeze–thaw (F/T) stress on o‐HSV was also examined. After one F/T cycle, a loss of infectious virus titers was observed. In addition, the monomeric virus particle concentration decreased during F/T stress, whereas there was a concurrent increase in larger particles (2–10 μm). The comprehensive biophysical characterization of viral stability conducted in this study identified major degradation events leading to loss of infectivity of o‐HSV and represents an important step toward stabilization of the virus against thermal and F/T stresses. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:485–494, 2015